Research on Teaching Reform of Intelligent Transportation System based on Internet Learning - Wei Dan; Wang Xiaolan; Ren Hongjuan (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2023)
Network learning education teaching method is widely used in the new era, is a new method of teacher teaching, new technology, is a new idea of school teaching management, is an important teaching tool for schools to organize online learning. Network learning has the characteristics of high technology value, high integration, high sharing and high personalization. Network teaching has its unique advantages and promotes the new development direction of teaching. At the same time, because of its own shortcomings, network teaching can not fully replace traditional teaching. This paper aims at the problems existing in intelligent transportation courses, combined with the advantages of network learning, to explore the reform of teaching methods and means, so as to improve the efficiency and quality of education and teaching, and enhance students' interest in learning.